Моделювання процесу гуманітарного розмінування із застосуванням робототехнічних комплексів військового призначення - Бондаренко, А. О. (ХНУРЕ, 2022)
The aim of the work is to model the process of humanitarian demining with the use of military robotic systems. One of the problems facing countries in all regions of the world, where hostilities have taken place or where military conflicts exist, is facing the problem of finding and identifying explosive devices. The search for and identification of anti-personnel mines and explosive devices is characterized by increasing attention to the problems of creating military robotic systems. The characteristics of military robotic complexes used in the process of humanitarian demining should be determined by complex modeling, which can be described using a semi-Markov model of its operation.
Keywords: humanitarian demining; military robotic systems; complex modeling